THE STRUCTURE OF HEMATITE (α-FE2O3) (001) SURFACES IN AQUEOUS MEDIA: SCANNING TUNNELING MICROSCOPY AND RESONANT TUNNELING CALCULATIONS OF COEXISTING O AND FE TERMINATIONS - Eggleston C.M.; Stack A.G.; Higgins S.R.; Bice A.M.; Boese S.W.; Pribyl R.D.; Nichols J.J.; Rosso K.M. (My University, 2003)
The iron oxide–water interface is of interest not only in geochemical and environmental processes, but also in fields ranging from corrosion to photocatalysis. The structure of α-Fe2O3 (001) surfaces is not fully understood, and questions have arisen recently concerning different terminations of (001) terraces; a so-called Fe-termination is expected, but under some conditions an O-termination may also be possible. Ultra-high vacuum (UHV) scanning tunneling microscope (STM) studies report evidence for an O-termination in coexistence with an Fe-termination, but other studies find no evidence for an O-termination. Molecular mechanics studies suggest that an O-termination should be possible in an aqueous environment. An O-termination could result from dissolution; if Fe atoms were to dissolve from an Fe-termination, an O-termination would presumably result (and vice-versa). We imaged hematite (001) surfaces in air and aqueous solution using STM. To aid interpretation of the images, we use a resonant tunneling model (RTM) parameterized using ab initio calculations.Our STM and RTM results are consistent with mixed O- and Fe-terminated (001) surfaces. For acid-etched surfaces we find evidence for a periodic (with wavelength of 2.2 ± 0.2 nm) arrangement of nominal O- and Fe-terminated domains. Two different borders between domains should occur, one in which the Fe-termination is high relative to the O-termination, and the reverse. The different domain borders have significantly different heights, consistent with RTM calculations. This agreement allows us to conclude that the Fe-termination is topographically high on most terraces. Surface domains are observed in aqueous solutions at the atomic scale, and appear to be very unreactive on tens-of-seconds time scales at pH 1.
Keywords: Hematite